Inter situ collections as a strategy to conserve an exceptional plant species from the Amazon rainforest - Diego Fernando Escobar Escobar; Markus Gastauer; Silvio Junio Ramos; Cecilio Frois Caldeira (PLoS ONE, 2026)
Ex situ conservation is essential for achieving the goals of the United Nations Global Strategy for Plant Conservation and the Sustainable Development Goals. Although seed banking is the most common method of ex situ plant conservation, many ecologically and economically important species cannot be effectively conserved by this method (i.e., exceptional species). These species can be preserved through cryopreservation and ex situ living collections; however, cryopreservation is expensive and remains underdeveloped for many taxa, while ex situ living collections often have poor genetic representation and limited evolutionary potential. Inter situ collections—conservation plantings established outside the current species range under natural or semi-natural conditions—are well suited for conserving the genetic diversity of exceptional species and can complement in situ conservation. Here, we present a case study establishing and managing inter situ collections of an exceptional plant species from the Amazon rainforest, aiming to preserve its genetic diversity in the long term and establish new self-sustaining populations. In addition, the inter situ collection contributes to ecological restoration by enriching the understory layer in recovering forest areas where the collection was established. Our study provides a model for initiatives seeking to develop seed sources for further conservation actions, such as reintroduction or habitat restoration. The results highlight the importance of systematically monitoring propagule production and field establishment success at the individual level in order to continuously optimize seed harvesting and propagation strategies. Finally, we propose practical guidelines for conserving plant species through inter situ collections, intended as an entry point rather than a comprehensive framework. We hope these findings encourage stronger integration between inter situ and in situ conservation approaches for exceptional tropical plant species .